(untitled) - Helgesen, Marc (New York, 1999)
Four Audio CDs are provided to supplement the listening tasks found in the Student's Book. The listening program is also available on Audio Cassettes.
Keywords: Listening,English language,Nghe,Tiếng Anh; Problems, exercises, etc,Study and teaching,Những vấn đề, các bài tập,...,Dạy và học